Dephosphorylation Passivates the Seeding Activity of Oligomeric Tau Derived From Alzheimer’s Brain - Wu, Ruozhen; Li, Longfei; Shi, Ruirui; Zhou, Yan; Jin, Nana; Gu, Jianlan; Tung, Yunn Chyn; Liu, Fei; Chu, Dandan (Frontiers in Molecular Neuroscience, 2021)
Accumulation of intracellular neurofibrillary tangles (NFTs), which are constituted of abnormally phosphorylated tau, is one of the neuropathological hallmarks of Alzheimer’s disease (AD). The oligomeric aggregates of tau in AD brain (AD O-tau) are believed to trigger NFT spreading by capturing normal tau as toxic seeds, in a prion-like fashion. Here we revealed the features of AD O-tau by Western blots using antibodies against various epitopes and determined the effect of dephosphorylation on the seeding activity of AD O-tau by capture and seeded aggregation assays. We found that N-terminal truncated and C-terminal hyperphosphorylated tau species were enriched in AD O-tau. Dephosphorylation of AD O-tau by alkaline phosphatase diminished its activity in capturing tau in vitro and in inducing insoluble aggregates in cultured cells. Our results suggested that dephosphorylation passivated the seeding activity of AD O-tau. Inhibition of phosphorylation may be a potent strategy to prevent the spreading of tau pathology.